The Reno-Vascular A2B Adenosine Receptor Protects the Kidney from Ischemia - Grenz, Almut (Public Library of Science, 2008)
BACKGROUND: Acute renal failure from ischemia significantly contributes to morbidity and mortality in clinical settings, and strategies to improve renal resistance to ischemia are urgently needed. Here, we identified a novel pathway of renal protection from ischemia using ischemic preconditioning (IP). METHODS AND FINDINGS: For this purpose, we utilized a recently developed model of renal ischemia and IP via a hanging weight system that allows repeated and atraumatic occlusion of the renal artery in mice, followed by measurements of specific parameters or renal functions. Studies in gene-targeted mice for each individual adenosine receptor (AR) confirmed renal protection by IP in A1(−/−), A2A(−/−), or A3AR(−/−) mice. In contrast, protection from ischemia was abolished in A2BAR(−/−) mice. This protection was associated with corresponding changes in tissue inflammation and nitric oxide production. In accordance, the A2BAR-antagonist PSB1115 blocked renal protection by IP, while treatment with the selective A2BAR-agonist BAY 60–6583 dramatically improved renal function and histology following ischemia alone. Using an A2BAR-reporter model, we found exclusive expression of A2BARs within the reno-vasculature. Studies using A2BAR bone-marrow chimera conferred kidney protection selectively to renal A2BARs. CONCLUSIONS: These results identify the A2BAR as a novel therapeutic target for providing potent protection from renal ischemia.